Semiotic Meanings of Artefacts in Toba Batak Ceremonies Across Some Regions In North Sumatera, Indonesia: A Study on Variations And Changes - Hutabarat, Horas; Sibarani, Berlin; Sumarsih, Sumarsih (Journal of Ecohumanism, 2025)
Toba Batak ethnic groups have resided in various sub-regions of Toba region of North Sumatera, Indonesia, since hundreds of years ago. They have practiced many ceremonies and used artefacts to support their cultural behaviours in practicing the ceremonies. Ceremonies of Baptism, Wedding, and Entering a New House practiced by the Batak ethnic groups in four sub-regions of Toba region: Sibisa, Limbong Sagala, Sait ni Huta, and Lumban Siagian were taken as the sources of data. This study was intended to find artefacts and meaning variations they put to them across the four sub-regions and changing of artefacts and their meanings across times and the sub-regions. To obtain the objectives, researcher used qualitative research of ethnographic design. The data were collected using interview and documentary techniques. The data were analysed in three cycling steps of data condensation, data display, and drawing and verifying conclusion techniques. The research results revealed: 11 out of 36 artefacts have meaning variations; and three artefacts get meaning changes across the four sub-regions. Based on the findings, attempts of preserving Toba Batak cultures are highly recommended by the old to the young generations. Government should facilitate for establishing institutions concerning ethnic cultures